PELAKSANAAN LAYANAN BIMBINGAN KONSELING DALAM UPAYA PENINGKATAN NILAI ISLAMI - Arisman Juanda (FITRAH: International Islamic Education Journal, 2023)
Efforts to increase the Islamic values of students and female students in preventing juvenile delinquency and counseling teachers play more roles in identifying and observing problems faced by students. The aim is to find out what material is applied in guidance and counseling services in an effort to increase Islamic values and what types of services are provided in an effort to increase Islamic values for students. The research method used is descriptive with a qualitative approach. The subjects of this study were guidance and counseling teachers who served at public high schools in the city of Banda Aceh according to the portion of the guidance and counseling teachers themselves. Data collection techniques using in-depth interviews and observation. Processing techniques and data analysis is done by way of qualitative descriptive analysis. The research results obtained from guidance and counseling service materials that are often applied in an effort to increase Islamic values relating to aspects of discipline, honesty, courtesy, cleanliness, peace-loving, courage to uphold the truth, shame in making mistakes, and trustworthiness include the application of the 5 daily prayers , obeying school rules, regarding tidiness, the lifestyle of a believer, signs of a hypocrite, the consequences and effects of cheating, the balance of words and deeds, respect for others, how to talk to younger, peers and older, governance good manners in association, good morality and attitude, clean is beautiful, cleanliness is part of faith, smiling and greeting is worship, relationships with others in Islam, defending the sanctity of religion and honor of the nation, shame on violating Islamic law, and shame not do God's commandments. Then the types of services provided in an effort to increase Islamic values include information services with a classical format, group guidance services with a group format, content services with an individual format, and individual counseling services with an individual format.